A comparison between the waist circumference of adult Filipino utilitarian cyclists and public utility vehicle users in Quezon City - Soriano IV, Herminio V. 1999-; Callanta, Hercules P. MSc. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
Following the outbreak of the Coronavirus Disease 2019 (COV1D-I9), it is observed how there is an increase in people engaging in utilitarian cycling over public utility vehicle (PUV) use, and also an increase in the rates of overweight and obesity. Previous researches have shown how engagement in utilitarian cycling leads to lower waist circumference, body mass index (BMI) and body fat percentages, implying its benefits in combatting the risk of overweight and obesity. However, most of these researches were conducted in developed countries. This study compared the waist circumference of utilitarian cyclists and PUV users, in the context of the Philippines, specifically in Quezon City, Metro Manila. Filipinos commuting within Quezon City, aged 18-60. were asked of their physical activity habits, reason for transportation preference, and travel activity, followed by measuring their waist circumference. 1 he data gathered was analyzed using an independent t-test. The study's findings may be significant for Filipinos, in particular utilitarian cyclists, those at risk of overweight and obesity, and PUV and active commuters. The study concluded that there is a significant difference between the waist circumference of male utilitarian cyclists and male PUV users, wherein the former was categorized as little to no risk for obesity while the latter was at a risk for obesity. Female PUV users were also reported to be at risk for obesity.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Cyclists; Commuters; Obesity; Physical fitness